KONSEP HYPNOPARENTING DAN RELEVANSINYA DENGAN PENDIDIKAN KARAKTER ANAK - Ike Ardiyanti (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2023)
The purposes of this research are: (1). To find out how to educate children using hypnoparenting, and (2). to find out the relevance of children's character education using hypnoparenting. This type of research is library research, the approach used is a literary approach. Data collection in this study is based on primary data and secondary data. The primary data in this study are books containing the concept of Hypnoparenting. In this research, data collection techniques used editing, organizing and analyzing techniques, as well as data analysis using descriptive analysis methods and using content analysis techniques. From the results of the study it was found that: (1). Applying hypnoparenting in educating children can be done by building closeness with children through communication before giving suggestions. Furthermore, when communicating and giving suggestions, it is better to use words that build and have a positive effect and are accompanied by physical touch so that the child feels loved. And more importantly, parents should give these suggestions repeatedly so that these suggestions stick in the child's subconscious mind. (2). The relevance of children's character education with the application of hypnoparenting found in this study includes objectives, mechanisms, and principles. The goal is the formation of noble character, while the mechanism is the subconscious mind which is then processed into the conscious mind, and finally the principle is the pattern of attitudes, words and behavior of the parents themselves or also called exemplary